PENGARUH PROBLEM BASED LEARNING TERHADAP PRESTASI BELAJAR IPAS DITINJAU DARI GAYA BELAJAR SISWA KELAS 3A - Widayanti, Ninik; Reffiane, Fine; Saputro, Susilo Adi (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2025)
Abstract: The purpose of this study was to determine the effect of problem based learning (PBL) on science learning achievement in terms of the learning styles of class 3A students at SDN Pandeanlamper 03 Semarang City. This study is a mix method study collaborating qualitative research and quantitative research using the Pre-Experimental research method of the One-Group Pretest-Posttest Design type. Qualitative data analysis techniques use observation guidelines and questionnaire respondents, while quantitative data use normality tests, paired sample t-tests, and N-Gain tests. The results of the study showed that the results of the observation sheet reached 73.9% and the student response questionnaire to problem based learning reviewed by learning styles showed 81.8%. While the posttest score increased compared to the pretest score, which was 89.11> 55.89. From the results of the paired sample t-test, a sig value of 0.000 <0.005 was obtained, so Ho was rejected and Ha was accepted. The results of the N-Gain test obtained data of 0.73, which means that the average value obtained after learning using the problem-based learning model in terms of student learning styles is included in the high category. This means that there is an influence of the Influence of Problem Based Learning (PBL) on Science Learning Achievement in terms of the Learning Style of Class 3A Students.